Investigation on characterization of different types of coals and preparation of coal-derived activated carbon - Purevsuren, Barnasan; Namkhainorov, Jargalsaikhan; Batbileg, Sanjaa; Jargalmaa, Soninkhuu (Proceedings of the Mongolian Academy of Sciences, 2024)
Activated carbon consumption is continuously increasing because of their application in such important areas as waste and drinkable water treatment, atmospheric pollution control, hazardous gas separation, cleaning of solvents, etc. Every year, Mongolia imports 700-800 tons of activated carbons for 700-900 USD per ton. We have selected 3 different types of coal, including a high ranking bituminous coal from Tavantolgoi deposit, stone sub-bituminous coal from Shariin Gol mine and brown lignite coal from Baganuur deposit and they were each enriched with heavy liquid, such as zinkum chlorade solution and processed by semicoking (carbonization) method to produce the main raw material for coal-derived active carbon. Using these carbonized coals, we have obtained coal-derived activeted carbon by activation with preheated water steam for 120 minutes. The most important technical properties of initial coal samples and activated carbons and their microporous properties, such as iodine number in percentage, methylene blue adsorption mg/g and surface area (BET)-m2/g were determined and characterized. The determined iodine number of activated carbon of purified and carbonized coals increased by 5-17 times and methylene blue adsorptions also increased from 4 to 10 times as compared to pyrolysis hard residue of initial coal samples without purification and activation. Basing on this, we are proposing a thecnological scheme for the production of coal-derived activated carbon.